Biologic Drugs as Analgesics for the Management of Low Back Pain and Sciatica. Issue 9 (20th December 2018) - Dimitroulas, Theodoros; Lambe, Tosin; Raphael, Jon H; Kitas, George D; Duarte, Rui V
Abstract: Objective: To discuss the current knowledge on the impact of commonly used biologic agents (i.e., anti–tumor necrosis factor–alpha [anti-TNF-α] and anti–nerve growth factor [anti-NGF]) in the management of low back pain with or without sciatica. Methods: A narrative literature review of studies investigating the use of biologic agents for the management of low back pain and sciatica was conducted. We searched MEDLINE and EMBASE for English language publications. A hand-search of reference lists of relevant studies was also performed. Results: Although some observational studies showed that inhibition of TNF-α reduced pain and improved function, randomized controlled trials and a meta-analysis failed to demonstrate the superiority of anti-TNF-α over placebo in this regard. Anti-TNF-α, however, reduced the risk of having invasive procedures such as discectomy and radicular block in cases of sciatica. Conversely, controlled studies showed moderate pain reduction and mild functional improvement with anti-NGF administration, but the side effect profile of anti-NGF was unfavorable compared with placebo. Conclusions: Overall, anticytokine treatments have limited efficacy in patients with chronic low back pain with or without sciatica. However, larger and better-designed studies may need to be performed in specific patient subpopulations. Low back pain is particularly disabling in younger patients. This group therefore represents a potential target population for investigating the effectiveness of anticytokine therapies, especially where other pharmacological and nonpharmacological management strategies have failed.